Análise de variáveis eletromiográficas e cinemáticas em protocolo incremental de corrida na esteira - Pereira, Fernanda Carolina [UNESP] (Universidade Estadual Paulista (Unesp), 2010)
Muscle fatigue is described as a cause of injuries among the many related to the running practice. Therefore, the purpose of this study was to analyze the behavior of the amplitude (RMS) and median frequency (MF) of EMG signal of the iliocostalis (CI), rectus femoris (RF), vastus lateralis (VL), vastus medialis (VM) biceps femoris (long head) (BFCL), tibialis anterior (TA) and gastrocnemius (lateral) (LNG) from the right lower limb, and the behavior of the parameters of amplitude (AP) and frequency (PF) spent in different percentages of the maximum speed during incremental protocol of treadmill running. 10 volunteers participated in this study, athletes, male, aged between 18 and 30 years with no history of injury in lower limbs and similar anthropometry. The protocol consisted of a treadmill test with initial velocity of 10 km.h-¹ and increments of 1 km.h-¹ each three minutes until volitional exhaustion, without rest interval. Synchronized collections were made of electromyographic and kinematic data. The signals were obtained through an acquisition module of biological signals (Telemyo 900 - Noraxon - USA) and software (Myoresearch - Noraxon - USA) calibrated with a sampling frequency of 1000 Hz, gain 2000 times. The raw data were filtered with a 60Hz notch filter, high pass and low pass 20Hz to 500Hz. To capture the image was used a digital video recorder (model NV-GS320, PANASONIC brand), and for image scanning and kinematic data collection was used the software Peak Motus 9.0 (ViconPeak). To obtain the values of RMS and FM analyzed the last ten passes of each speed through a specific routine (Matlab). To obtain these variables AP (m) and FP (stride I min) were analyzed for the last ten past each speed, using specific software (Peak Motus 9.0). After verification of data normality (Shapiro-Wilk) and homogeneity of the data (Levene), the comparison ...(Complete abstract click electronic access below)

A fadiga muscular é descrita como uma das causas de lesões dentre as muitas relacionadas á prática da corrida. Diante disso, o objetivo do presente estudo foi analisar o comportamento da amplitude (RMS) e freqüência mediana (FM) do sinal eletromiográfico dos músculos iliocostal (IC), reto femoral (RF), vasto lateral (VL), vasto medial (VM), bíceps femoral (cabeça longa) (BFCL), tibial anterior (TA) e gastrocnêmio (porção lateral) (GNL) do membro inferior direito, e o comportamento dos parâmetros de amplitude (AP) e freqüência (FP) da passada em diferentes porcentagens da velocidade máxima, durante protocolo incremental de corrida em esteira. Participaram desse estudo 10 voluntários, atletas, do sexo masculino, com idade entre 18 e 30 anos, sem antecedentes de lesão nos membros inferiores e antropometria semelhante. O protocolo foi composto por um teste em esteira com velocidade inicial de 10 km.h-¹ e incrementos de 1 km.h-¹ a cada três minutos, até a exaustão voluntária, sem intervalo para descanso. Foram realizadas coletas sincronizadas dos sinais eletromiográficos e dos dados cinemáticos. Os sinais eletromiográficos foram obtidos por meio de um módulo de aquisição de sinais biológicos (Telemyo 900 - Noraxon - EUA) e de um software (Myoresearch - Noraxon - EUA) calibrado com freqüência de amostragem de 1000 Hz, ganho de 2000 vezes. Os dados brutos foram filtrados com filtro notch 60Hz, passa alta de 20Hz e passa baixa de 500Hz. Para captação da imagem foi utilizada uma filmadora digital (modelo NV-GS320, da marca PANASONIC), e para digitalização da imagem e obtenção dos dados cinemáticos foi utilizado software PEAK MOTUS 9.0 (ViconPeak). Para obtenção dos valores de RMS e FM foram analisadas as dez últimas passadas de cada velocidade, por meio de rotina específica (Matlab). Para obtenção das variáveis ...(Resumo completo, clicar acesso eletrônico abaixo)
Keywords: Cinesiologia; Eletromiografia; Biomecânica; Fadiga muscular